Apresentação Clínica da Intolerância Hereditária à Frutose Prévia à Diversificação Alimentar. O Papel dos Excipientes - Dias, Filipa Mestre A. (2015)
We report a case of hereditary fructose intolerance (HFI) with clinical onset prior to beikost: A two-month-old infant who had a first symptomatic hypoglycemic episode (generalized motor epileptic crisis) during a febrile respiratory infection with dyspnoea, while medicated with clarithromycin and betamethasone oral formulations. At nine months he presented a new hypoglycemic episode two hours after eating a flavored yogurt. The hepatomegaly and laboratory findings suggested the diagnosis of Von Gierke’s disease, not confirmed by molecular studies. There after, mother reported repeated vomiting episodes two hours after the ingestion of certain foods, leading to the clinical suspicion of HFI, subsequently confirmed by genetic analysis. There are few cases reporting metabolic decompensation of HFI prior to complementary feeding, mainly in exclusively breastfed children. We concluded that some routine formulations have excipients that can precipitate metabolic decompensation in HFI.